Pancreatic gene variants potentially associated with dipeptidyl peptidase-4 inhibitor treatment response in Type 2 diabetes. (February 2014) - Jamaluddin, Jazlina Liza; Huri, Hasniza Zaman; Vethakkan, Shireene Ratna; Mustafa, Norlaila
In the adult pancreas, the expression of the genes PAX4, KCNQ1, TCF7L2, KCNJ11, ABCC8, MTNR1B and WFS1 are mainly restricted to β cells to maintain glucose homeostasis. We have identified these genes as the main regulators of incretin-mediated actions, and therefore they may potentially influence the response of DPP-4 inhibitors. This review represents the first detailed exploration of pancreatic β-cell genes and their variant mechanisms, which could potentially affect the response of DPP-4 inhibitors in Type 2 diabetes. We have focused on the signaling pathways of these genes to understand their roles in gastrointestinal incretin-mediated effects; and finally, we sought to associate gene mechanisms with their Type 2 diabetes risk variants to predict the responses of DPP-4 inhibitors for this disease.